E-faculty: Postgraduate Information System / Ng Theen Weng - Ng, Theen Weng (2001)
The computer industry has gone through a dramatic change since its first introduction, about 30 years ago. Information technology has pushed us to a degree of revolution that we could not have possibly foreseen in the last 30 years or so. Changes include many aspects such as business, games, education, administration and politics and most of all, our daily life. This thesis is about the introduction of the usage of information technology in full force to the local higher-learning institution: university. In the process, a new system for managing the postgraduate information will be introduced and how it will tackle the latest problems in the administration of this information.